2003
DOI: 10.1055/s-2003-43231
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Pigmented Villonodular Synovitis

Abstract: Pigmented villonodular synovitis (PVNS) is a rare, benign, idiopathic proliferative disorder of the synovium that results in villous and/or nodular formation in joints, tendon sheaths, and bursae. The disease can be localized or diffuse. Patients with this condition typically present with symptoms of mild discomfort and associated stiffness of the involved joint; however, the spectrum of presentations is broad. Diagnosis of PVNS can be clinically difficult, and plain radiographs are usually nonspecific. Magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…If enhancement is observed, it is usually caused by inflammation and increased vascularity of the synovium. More often, delayed enhancement of the solid component is observed [5] , [6] . Although these features are classic for PVNS on imaging, it should be noted that cases present with variable signal intensity depending on the degree of hemosiderin deposition.…”
Section: Discussionmentioning
confidence: 99%
“…If enhancement is observed, it is usually caused by inflammation and increased vascularity of the synovium. More often, delayed enhancement of the solid component is observed [5] , [6] . Although these features are classic for PVNS on imaging, it should be noted that cases present with variable signal intensity depending on the degree of hemosiderin deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the TGCT usually occurs in all decades of life with predominance in the third or fourth decade. [7] The etiology of TGCT is controversial, someone has suggested that recurrent trauma and hemarthrosis may be the contributing factor. [8] Microscopically, the tumor is composed of monocyte, multinucleated giant cells and foam cells distributing in a fibrous stroma, presenting hemosiderin deposition.…”
Section: Discussionmentioning
confidence: 99%
“…MRI typically demonstrates a mass-like synovial proliferation with lobulated margins. 10 , 22 This may be extensive in the diffuse form or limited to a well-defined single nodule in the localized form. The signal characteristics include low-to-intermediate signal on T 1 weighted images, variable enhancement following gadolinium, 23 low-to-intermediate signal on T 2 weighted images with some areas of high signal owing to joint fluid or an inflamed synovium.…”
Section: Discussionmentioning
confidence: 99%